GROUND-FAULT PROTECTION SCHEME FOR AN EMERGENCY OR STANDBY POWER SYSTEM WITH MULTIPLE NEUTRAL-TO-GROUND CONNECTIONS. - Liew, A.C. (2014)
Conference Record - IAS Annual Meeting (IEEE Industry Applications Society)